Intersigmoid Internal Hernia: Laparoscopic Repair of a Rare Cause of Bowel Obstruction - Ebrahim Almahmeed; Hasan Shawqi Aljawder; Mohamed Khalid Fadhul; Abdulmenem Abualsel (Case Reports in Surgery)
Intersigmoid hernia is a hernia of an abdominal viscus into the intersigmoid fossa, and it is one of the rare forms of internal hernia that can present with bowel obstruction. Intersigmoid hernia poses challenges in its diagnosis and treatment due to its rarity and vague signs and symptoms. As such, a high index of suspicion should be maintained, and early diagnostic examination should be done that includes an abdominal CT that may show signs suggestive of internal hernia. Managing this condition relies mainly on surgical intervention (open or laparoscopic) in a timely manner to prevent further complications, such as bowel ischemia. We present a case of intersigmoid hernia in a 51-year-old Bahraini male who presented with vague abdominal pain and vomiting.